2015
DOI: 10.1139/cgj-2014-0209
|View full text |Cite
|
Sign up to set email alerts
|

Capacity of dynamically installed anchors as assessed through field testing and three-dimensional large-deformation finite element analyses

Abstract: The capacity of dynamically installed anchors in soft normally consolidated clay was examined experimentally through a series of field tests on a 1:20 reduced-scale anchor. The anchors were installed through free fall in water, achieving tip embedment of 1.5–2.6 times the anchor length, before being loaded under undrained conditions at various load inclinations. Vertical anchor capacities were between 2.4 and 4.1 times the anchor dry weight and were satisfactorily predicted using the American Petroleum Institu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Following the study by O'Beirne et al (2015), the pull-out capacity is plotted as the normalized V-H envelope (H/H 0 versus V/V 0 ) in Figure 4. 2, 2.4 and 3 were selected in this study.…”
Section: Effect Of Embedment Ratiomentioning
confidence: 99%
“…Following the study by O'Beirne et al (2015), the pull-out capacity is plotted as the normalized V-H envelope (H/H 0 versus V/V 0 ) in Figure 4. 2, 2.4 and 3 were selected in this study.…”
Section: Effect Of Embedment Ratiomentioning
confidence: 99%
“…It has also been used for temporary facilities in the Gulf of Mexico (Zimmerman et al 2009), although the design used in the Gulf of Mexico is quite different to that used offshore Brazil. The majority of performance data are from centrifuge studies (O'Loughlin et al 2004Richardson et al 2006Richardson et al , 2009Gaudin et al 2013;Hossain et al 2015) although a growing body of field experience is becoming available (Zimmerman et al 2009, O'Beirne et al 2015.…”
Section: Performance Data and Technology Maturity Of Each Anchor Typementioning
confidence: 99%
“…Torpedo anchor and DEPLA data from reduced-scale field tests reported by and O'Beirne et al (2015) are shown in Figure 4. Again, capacity is seen to increase with depth as expected for this site which has an undrained shear strength gradient of about 1.5 kPa/m (over the depth range shown in Figure 4).…”
Section: Performance Data and Technology Maturity Of Each Anchor Typementioning
confidence: 99%
“…Lieng et al (2000) performed wished-in-place analysis with small strain theory using Abacus/Standard. Large-deformation FE (LDFE) analyses on pre-embedded anchors (or wished-in-place) in ideal Tresca material ignoring the influence of installation were carried out by O'Loughlin (2014) andO'Beirne et al (2015). They noted that conventional small strain FE analyses result in ever-increasing load magnitudes where the calculation is forced to stop due to severe entanglement of soil elements, necessitating to set some mandatory criteria to define the ultimate capacity such as the capacity achieved prior to such severe entanglement.…”
Section: Introductionmentioning
confidence: 99%
“…Although they tried to consider a specific element type, it is not a true LDFE method unless the distorted soil elements solve, with all of them being either limited to small strain analyses (Lieng et al, 2000;de Sousa et al, 2011) or pre-embedded anchors (or wished-in-place) in ideal Tresca material ignoring the influence of installation (Wang & O'Loughlin, 2014;O'Beirne et al, 2015).…”
Section: Introductionmentioning
confidence: 99%